Ongoing Oxidative Stress Causes Subclinical Neuronal Dysfunction in the Recovery Phase of EAE - Radbruch, Helena; Bremer, Daniel; Guenther, Robert; Cseresnyes, Zoltan; Lindquist, Randall; Hauser, Anja E.; Niesner, Raluca (Frontiers in Immunology, 2016)
Most multiple sclerosis patients develop over time a secondary progressive disease course, characterized histologically by axonal loss and atrophy. In early phases of the disease, focal inflammatory demyelination leads to functional impairment, but the mechanism of chronic progression in multiple sclerosis is still under debate. Reactive oxygen species generated by invading and resident central nervous system (CNS) macrophages have been implicated in mediating demyelination and axonal damage, but demyelination and neurodegeneration proceed even in the absence of obvious immune cell infiltration, during clinical recovery in chronic multiple sclerosis. Here, we employ intravital NAD(P)H fluorescence lifetime imaging to detect functional NADPH oxidases (NOX1-4, DUOX1,2) and, thus, to identify the cellular source of oxidative stress in the central nervous system of mice affected by experimental autoimmune encephalomyelitis (EAE) in the remission phase of the disease. This directly affects neuronal function in vivo, as monitored by cellular calcium levels using intravital FRET-FLIM, providing a possible mechanism of disease progression in multiple sclerosis.